Preliminary analysis of loss rates of honey bee colonies during winter 2015/16 from the COLOSS survey. Issue 5 (5th December 2016) - Brodschneider, Robert; Gray, Alison; van der Zee, Romée; Adjlane, Noureddine; Brusbardis, Valters; Charrière, Jean-Daniel; Chlebo, Robert; Coffey, Mary F; Crailsheim, Karl; Dahle, Bjørn; Danihlík, Jiří; Danneels, Ellen; et al.
Abstract : In this short note we present comparable loss rates of honey bee colonies during winter 2015/16 from 29 countries, obtained with the COLOSS questionnaire. Altogether, we received valid answers from 19, 952 beekeepers. These beekeepers collectively wintered 421, 238 colonies, and reported 18, 587 colonies with unsolvable queen problems and 32, 048 dead colonies after winter. This gives an overall loss rate of 12.0% (95% confidence interval 11.8–12.2%) during winter 2015/16, with marked differences among countries. Beekeepers in the present study assessed 7.6% (95% CI 7.4–7.8%) of their colonies as dead or empty, and 4.4% (95% CI 4.3–4.5%) as having unsolvable queen problems after winter. The overall analysis showed that small operations suffered higher losses than larger ones. A table with detailed results and a map showing response and relative risks at regional level are presented.